Post ≠ Post: An Experimental Study on Corporate Brand Posts on Facebook - Markus Kick (Springer Gabler, 2015)
Brand presences on social network sites (SNSs) like Facebook, Twitter, or Google+ form important communication tools for marketers in the social media environment. Engaging the consumer in an ongoing dialogue via brand fan pages, especially on Facebook, becomes more and more important. However, evidence about what drives a successful Facebook brand post is scarce. By means of a field experimental study over a two week treatment period, I study the effect of corporate brand posts on brand fans' post recall capability, attitude toward the brand, and purchase intention. I manipulate the degree of brand post interactivity and vividness and the underlying degree of product involvement by posting on two different brand fan pages. Results indicate that Facebook brand posts are able to positively influence fans' attitude toward the brand. The degree of interactivity and vividness positively moderates the main effect as posts with a high degree of interactivity and vividness cause a higher change in attitudinal measures than low interactive and vivid posts. Further, Facebook brand fans are able to better recall posts from high involvement brands due to selective perception effects in the distractive Facebook environment. On the contrary, posts are more effective on fans' attitude toward the brand when posted from a fan page with a comparably lower involvement level. Facebook brand posts activate peripheral routes of information processing which are in favor for communication needs of low involvement products. In addition, a significant interaction effect between the level of involvement and the degree of interactivity and vividness is found. Highly interactive and vivid brand posts are more successful when posted by a low involvement product or brand. Implications for marketing research and practitioners are discussed.
Additional information: Reworking Story for a practitioners target group. Cf. Kick M. (2015): Selected Essays on Corporate Reputation and Social Media. Springer Gabler, Wiesbaden, https://doi.org/10.1007/978-3-658-08837-8
Keywords: 330; Social Media; Interactivity; Brand Posts; Vividness; Facebook